Primary syphilis without chancre – A case report of rare syphilitic balanitis of Follmann - Ren, Xu-qi; Nie, Qun-ling; Liu, An-qi (Frontiers in Medicine, 2022)
Introduction Syphilitic balanitis of Follmann (SBF) is a rare condition of primary syphilis which is characterized by any kind of balanitis with or without chancre on the penis combined with the presence of swollen inguinal lymph nodes confirmed by the finding of Treponema pallidum in the lesions or by the positive serological syphilitic testing. Timely identification of the SBF is very important in properly treating the disease stopping the spread of syphilis. Case presentation A 42year-old heterosexual male patient came to our clinic and complained of a painless, hard erythema nodule with a whitish scale in his coronal sulcus of the penis for about a week. The dermatologic examination revealed an infiltrative, hard erythematous lesion surrounding the coronal sulcus of the patient’s penis, with mild erosion and a small amount of exudation. There was a whitish pseudomembrane-like covering on the surface of the erythematous lesion in the coronal sulcus, which is mimicked as candidal balanitis. The result of the fungus microscopic examination was negative, while the laboratory findings showed positive results in serologic syphilitic testing. The patient was diagnosed with primary syphilis and intramuscularly treated with a dose of benzylpenicillin of 2.4 million units. The patient’s skin lesions disappeared completely 60 days after penicillin treatment. Conclusion To our knowledge, this is the first SBF case reported in China. Syphilitic balanitis of Follmann may have variable clinical appearances. We emphasize that when balanitis with risky sexual activities or with sexually transmitted diseases, the diagnosis of SBF should be kept in mind.